2007
DOI: 10.1002/eji.200737461
|View full text |Cite
|
Sign up to set email alerts
|

PD‐L2 expression extends beyond dendritic cells/macrophages to B1 cells enriched for VH11/VH12 and phosphatidylcholine binding

Abstract: B1 B cells are the major source of natural antibody that is essential for innate immunity. The B1 repertoire is skewed toward production of phosphatidylcholine (PtC)-binding V H 11 and V H 12 immunoglobulin that plays a key role in immune defense against bacterial infection. Programmed death-ligand 2 (PD-L2) is a ligand for the immunosuppressive receptor programmed death-1 (PD-1). It has been reported that expression of PD-L2 is restricted to dendritic cells and macrophages in mice. Here we show that 50-70% of… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

4
161
0
2

Year Published

2008
2008
2023
2023

Publication Types

Select...
10

Relationship

1
9

Authors

Journals

citations
Cited by 173 publications
(167 citation statements)
references
References 28 publications
4
161
0
2
Order By: Relevance
“…2 A and B), reducing both B1a and B1b subsets in the spleen. To assess B1 function, we measured the number of spontaneous IgM anti-PC antibody-producing cells, because B1 cells are the main producers of such antibodies (15). The numbers of these cells were similar in both spleen and PerC in mice treated with anti-BLyS or isotype control antibody, although variance in the spleen was higher in controls (Fig.…”
Section: Resultsmentioning
confidence: 99%
“…2 A and B), reducing both B1a and B1b subsets in the spleen. To assess B1 function, we measured the number of spontaneous IgM anti-PC antibody-producing cells, because B1 cells are the main producers of such antibodies (15). The numbers of these cells were similar in both spleen and PerC in mice treated with anti-BLyS or isotype control antibody, although variance in the spleen was higher in controls (Fig.…”
Section: Resultsmentioning
confidence: 99%
“…Although these data were subsequently partially refuted by other results showing that PD-L2 can play a role in EAE in some mice strains (16), we felt supported in our decision by the observation that the expression of PD-L2 is much more restricted than that of PD-L1. Thus, whereas PD-L1 is constitutively expressed on a wide range of hematopoietic and nonhematopoietic cells (46,51,52), PD-L2 is only inducible expressed in dendritic cells, macrophages, and mast-cells (46,(51)(52)(53). Incubation of PBMC of AMS patients with PD-1-specific neutralizing Abs resulted in the increased proliferation of MBP-specific CD4 ϩ and CD8 ϩ T lymphocytes.…”
Section: Discussionmentioning
confidence: 99%
“…It is widely known that the two PD-1 ligands differ in their expression patterns: PD-L1 is expressed on T cells, B cells, dendritic cells, macrophages, nonhematopoietic and other cell types, while expression of PD-L2 is much more restricted to dendritic cells, B1 cells, and macrophages (16,26). Here, we found that both PD-1 ligands were inducibly expressed on T cells from tuberculosis patients in response to M. tuberculosis, demonstrating for the first time that PD-L2 is expressed on human T cells.…”
Section: Discussionmentioning
confidence: 99%